Achieving the dehydriding reversibility and elevating the equilibrium pressure of YFe2 alloy by partial Y substitution with Zr. (2nd August 2018) - Pang, Haoliang; Li, Ziming; Zhou, Chao; Wang, Hui; Ouyang, Liuzhang; Yuan, Shurong; Zhao, Yujun; Zhu, Min
Abstract: To overcome the hydrogen-induced amorphization and phase disproportionation in the fast de-/hydrogenation of YFe2, the alloying of partial substituting Y with Zr was carried out to obtain Y 1−x Zr x Fe 2 ( x  = 0.1, 0.2, 0.3, 0.5) alloys. All YZrFe alloys remained single C15 Laves phase structure at states of as-annealed, hydrogenated and dehydrogenated. With the increasing of Zr content, the YZrFe alloys showed the decrease in the lattice constants and hydrogenation capacity, but the increase in the dehydrogenation capacity and dehydriding equilibrium pressure. The alloy Y0.9 Zr0.1 Fe2 showed maximum initial hydrogenation capacity of 1.87 wt% H, while the alloy Y0.5 Zr0.5 Fe2 showed highest desorption capacity of 1.26 wt% with obvious dehydriding plateau. Based on experiment analysis and first principle calculation of binding energy, the great improvement in the dehydriding thermodynamics for YZrFe alloys is attributed to the change in the unit cell volume, electron concentration and stability of hydrides due to the Zr substitution. Highlights: The hydrogen-induced amorphization and disproportionation were eliminated by partially substituting Y with Zr in YFe2 . The Y-Zr-Fe alloys show the increase in the reversible capacity and dehydriding equilibrium pressure with increasing Zr content. The alloy Y0.5 Zr0.5 Fe2 even delivered a short dehydriding plateau in the PCI curve.